Interleukin-10 controls human peripheral PMN activation triggered by lipopolysaccharide - Martire Greco, Daiana (2013)
Large amounts of anti-inflammatory mediators, such as interleukin (IL)-10, are produced and found early in the course of sepsis. We explore the role of IL-10 on neutrophil (PMN) activation/function using an in vitro model. Isolated human PMN were pre-incubated with polysaccharide (LPS) and/or IL-10 for 18 h. Subsequently, a second LPS exposure was performed and CD11b and CD66b up-regulation, and the reactive oxygen species (ROS) generation were measured 2 h later. We found that IL-10 prevented PMN activation and the secretion of TNF-a and IL-8 induced by the first LPS contact. In the absence of IL-10, a second LPS exposure induced additive effects that were prevented by IL-10. Only ROS generation was highly affected by the blockade of PMN-secreted TNF-a or IL-8. Additionally, IL-10 prevented other possible mechanisms of LPS priming. Therefore, IL-10 modulates PMN activation preventing autocrine activating loops and priming mechanisms, rendering PMN less responsive to a second LPS exposure.